The Effect of the Aerial Part of Lindera akoensis on Lipopolysaccharides (LPS)-Induced Nitric Oxide Production in RAW264.7 Cells - Yang, Chung-Ping (Molecular Diversity Preservation International (MDPI), 2013)
Four new secondary metabolites, 3α-((E)-Dodec-1-enyl)-4β-hydroxy-5β-methyldihydrofuran-2-one (1), linderinol (6), 4′-O-methylkaempferol 3-O-α-l-(4″-E-p-coumaroyl)rhamnoside (11) and kaempferol 3-O-α-l-(4″-Z-p-coumaroyl) rhamnoside (12) with eleven known compounds—3-epilistenolide D(1) (2), 3-epilistenolide D(2) (3), (3Z,4α,5β)-3-(dodec-11-ynylidene)-4-hydroxy-5-methylbutanolide (4), (3E,4β,5β)-3-(dodec-11-ynylidene)-4-hydroxy-5-methylbutanolide (5), matairesinol (7), syringaresinol (8), (+)-pinoresinol (9), salicifoliol (10), 4″-p-coumaroylafzelin (13), catechin (14) and epicatechin (15)—were first isolated from the aerial part of Lindera akoensis. Their structures were determined by detailed analysis of 1D- and 2D-NMR spectroscopic data. All of the compounds isolated from Lindera akoensis showed that in vitro anti-inflammatory activity decreases the LPS-stimulated production of nitric oxide (NO) in RAW 264.7 cell, with IC(50) values of 4.1–413.8 μM.